Determinan Penyakit Jantung dan Pembuluh Darah Pasien Rawat Jalan Poli Jantung dan Poli Penyakit Dalam RSD dr. Soebandi Jember (Determinants of Heart and Blood Vessel Disease at Cardiovascular and Internal Medicine Outpatients Clinic in dr. Soebandi General Hospital of Jember ) - Sulis Tiani; Pudjo Wahjudi; Dwi Martiana Wati (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Heart and blood vessel disease (HBVD) is a disease that attacks heart and bloodvessels that cause disorder in these organs. Heart and blood vessel disease (HBVD) is apublic health problem and is the most leading cause of death in Indonesia. Prevalence ofHBVD have increased 15% in January up to December 2014 in dr. Soebandi generalhospital. The research is done in outpatiens at cardiovascular and internal medicineclinic in dr. Soebandi general hospital in April 2015. This research aimed to describe andanalyze the risk factors of HBVD in dr. Soebandi general hospita of Jemberl. Theresearch was conducted by case control design. An age over 55 years (p=0.03), BMIwith fat (p=0.004), alcohol consumption (p=0.015), smoking habit over 10 per day(p=0,0018), and the consumption of foods with high amount of saturated fat (p=0.0018)were significant correlated with HBVD. The highest risk factor was smoking habit withover 20 per day had a risk 15,8 times higher than non-smokers, while the lowest was theBMI with fat had a risk 3,6 times higher than normal BMI.Keywords: Risk factor, Heart and blood vessel disease